PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, SANKSI PAJAK DAN AKUNTABILITAS PELAYANAN PUBLIK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KABUPATEN WONOGIRI - Eryanti, Rahma; Harimurti, Fadjar; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
This study aims to examine and analyze the effect of understanding taxregulations, tax sanctions, and public service accountability on taxpayercompliance in paying motorized vehicle taxes at the UPPD-SAMSAT Office ofWonogiri Regency. The type of data used is qualitative and quantitative data. Thepopulation in this study were all motor vehicle taxpayers registered at the UPPDSAMSATOffice of Wonogiri Regency in 2019. This study used secondary dataand primary data of 100 samples with the sampling method using accidentalsampling. Data collection techniques were carried out through the method ofdocumentation and questionnaires at the UPPD-SAMSAT Wonogiri office. Thedata analysis technique used is multiple linear regression analysis. The results ofthis study indicate that the variable understanding of tax regulations, taxsanctions, and public service accountability has a significant positive effect ontaxpayer compliance in paying motorized vehicle taxes at the UPPD-SAMSATOffice of Wonogiri Regency.